6(x-9)=-65

Simple and best practice solution for 6(x-9)=-65 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(x-9)=-65 equation:



6(x-9)=-65
We move all terms to the left:
6(x-9)-(-65)=0
We add all the numbers together, and all the variables
6(x-9)+65=0
We multiply parentheses
6x-54+65=0
We add all the numbers together, and all the variables
6x+11=0
We move all terms containing x to the left, all other terms to the right
6x=-11
x=-11/6
x=-1+5/6

See similar equations:

| 21x^2-1050x+50=0 | | 2(x-2)-2=13 | | 3x/2-5=16 | | x+.1=300 | | x(.1)=300 | | -12x-7=-3x+2 | | -12x-7=3x+2 | | (x+5)/(x-5)=10 | | g+(-0.8=-2 | | 50+-10x+-15x2+x3+x4=0 | | p+-26=-13.8 | | 5x-33=2x-21 | | 1.5+x=0.5+2x | | 2X+0.1x=6 | | 2x^2+26x+59=0 | | -13c=2 | | X+0.2x=6 | | 90+c=37 | | c-10=5 | | 3z+3-1=2z+1 | | 11a+6=10a+7 | | 3x/5+3=7 | | 4m-22m=6 | | 9b+3=6b+4 | | (3−6x)​2​​=6 | | (3−6x)​2​​-6=0 | | -6y+24=-9 | | 8a-21=0 | | 11-60y=92 | | 2y-72=-91 | | 18x+57=52 | | -9y=60 |

Equations solver categories